2006
DOI: 10.1159/000097098
|View full text |Cite
|
Sign up to set email alerts
|

Acylated Ghrelin Secretion Is Acutely Suppressed by Oral Glucose Load or Insulin-Induced Hypoglycemia Independently of Basal Growth Hormone Secretion in Humans

Abstract: Background: Ghrelin has been reported to be the natural ligand of growth hormone (GH) secretagogue receptor, and it is known that exogenous ghrelin administration strongly stimulates GH release in humans. However, the effects of endogenous ghrelin on GH secretion and changes in ghrelin levels during dynamic changes in GH levels are not well understood. Methods: Therefore, we measured circulating acylated ghrelin concentrations during oral glucose tolerance tests (OGTTs) in patients with active acromegaly (AA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 91 publications
1
8
1
1
Order By: Relevance
“…Taken together, it would be teleologically meaningful if AG levels are suppressed by insulin and stimulated by hypoglycemia. This study demonstrates that AG and UAG measured by updated assays are initially suppressed by hyperinsulinemia, which is in concordance with studies using older assays (8,9,10,11). Our study demonstrates an independent effect of acute hyperinsulinemia on both AG and UAG levels in the absence of a change in plasma glucose levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, it would be teleologically meaningful if AG levels are suppressed by insulin and stimulated by hypoglycemia. This study demonstrates that AG and UAG measured by updated assays are initially suppressed by hyperinsulinemia, which is in concordance with studies using older assays (8,9,10,11). Our study demonstrates an independent effect of acute hyperinsulinemia on both AG and UAG levels in the absence of a change in plasma glucose levels.…”
Section: Discussionsupporting
confidence: 91%
“…Among these effects, glucoregulatory properties seem to be important (5) and ghrelin-deficient mice developed profound hypoglycemia during calorie restriction (7). In response to insulin-induced hypoglycemia, however, total (8,9) as well as AG (10) and UAG (11) levels decrease rather than increase in human subjects, irrespective of GH status (12). Whether this discrepancy reflects reciprocal effects of insulin and hypoglycemia per se remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, it still remains to be elucidated which factor ultimately controls this stimulation of GH release in response to stress. Previous insulin tolerance test studies on total and acylated ghrelin demonstrated that insulin-induced hypoglycemia did not suppress the ghrelin secretion and GH might not be regulated by ghrelin [17][18][19]. In our study, GH levels were elevated whereas total ghrelin levels were decreased, and the total ghrelin levels were lower in the subjects with inhalation burn compared with the subjects without inhalation injury.…”
Section: Discussioncontrasting
confidence: 47%
“…It interacts with the GH secretagogue receptor type 1a (GHSR1a) and stimulates GH secretion. The ratio between both ghrelin forms (acylated and desacylated ghrelin) is calculated to be about 1 according to Moller et al The ratio between both ghrelin forms is closely maintained after food intake (41) or during oral glucose load (40). According to Kim et al (40), these findings are independent of GH levels.…”
Section: Discussionmentioning
confidence: 99%